Inferences during Reading - O'Brien, Edward J.; Cook, Anne E.; Lorch, Jr, Robert F. (Cambridge : Cambridge University Press, 2015)
Inferencing is defined as'the act of deriving logical conclusions from premises known or assumed to be true', and it is one of the most important processes necessary for successful comprehension during reading. This volume features contributions by distinguished researchers in cognitive psychology, educational psychology, and neuroscience on topics central to our understanding of the inferential process during reading. The chapters cover aspects of inferencing that range from the fundamental bottom-up processes that form the basis for an inference to occur, to the more strategic processes that transpire when a reader is engaged in literary understanding of a text. Basic activation mechanisms, word-level inferencing, methodological considerations, inference validation, causal inferencing, emotion, development of inferences processes as a skill, embodiment, contributions from neuroscience, and applications to naturalistic text are all covered as well as expository text, online learning materials, and literary immersion.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Keywords: Inference; Cognitive psychology